AUTOMATIC IDENTIFICATION OF SUBMARINE LANDFORMS USING OBJECT BASED IMAGE ANALYSIS IN THE AREA OF NORTH AEGEAN BASIN - Argyropoulou, E.; Argialas, D.; Nomikou, P.; Papanikolaou, D.; Dekavalla, M. (Bulletin of the Geological Society of Greece, 2016)
This paper is focused on the study of the North Aegean seabed, from a Digital Seabed Elevation Model (DSEM), by employing Object Based Image Analysis (OBIA). The goal is the automatic extraction of geomorphological features based on morphological criteria, in the North Aegean Basin. A Digital Seabed Elevation Model (DSEM) of 150x150 meters resolution was employed. At first, slope gradient, profile curvature, and percentile were derived from this DSEM. Four different layers of segmentation were created in order to extract the final geomorphological classes, discontinuities, faults like and fault surface in the final segmentation of level 4. On previous levels, more geomorphological features were also classified such as continental platform and continental slope. The results were evaluated qualitatively and quantitatively, through a tectonic map which has been created manually based on the analysis of seismic profiles. The results of the comparison of the two methods were satisfactory. Thus, the developed OBIA method is considered successful.